CORPUS OF PUNISHMENT: CONCEPT, STRUCTURE, CONTENT (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the conceptualization of the corpus (composition) of punishment. In a narrow sense, the composition of the punishment is proposed to be understood as a system of objective and subjective signs of state influence on the person of the convicted person, which define it as a punishment. In a broad sense, it is an analytical construct that expresses the objective and subjective orientation, content, means and process of execution and serving of punishment. The composition of the punishment includes four elements: the object and the objective side, the subject and the subjective side. The object is three-dimensional. His first plan is represented by the personality of the convict. The second is the components of the environment and situation of committing a criminal offense. The third plan is the identity of the victim (if available).As a result, punishment is proposed to be understood as a measure of legal influence implemented on behalf of the state based on a court verdict against a person found guilty of a criminal offense by limiting the rights and freedoms of the convicted person as provided by law, as well as against other persons through the demonstration and/or dissemination of information about criminal enforcement practice. Punishment is intended to punish, as well as to help prevent the convict from committing new criminal offenses.
Keywords: punishment; composition of punishment; convicted; execution; serving; correction; resocialization; prevention; criminal offense; crime